Pertumbuhan Mencit (Mus Musculus L.) Setelah Pemberian Biji Jarak Pagar (Jatropha curcas L.) - Muliani, Hirawati (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
The research of white mouse growth after was given with barbados nut’s seed is aimed to know about the effect of barbados nut’s seed on the growth of female white mouse. Thirty two female white mouse were acclimated during 1 week and then alloted into 2 groups, each group was treated as follows : P0 (control): were giving of aquadest; P1: were giving of 0,2 grams barbados nut’s seed powder daily per mouse. Barbados nut’s seed powder were given by pipet to the mouth of the mouse. Long of the treatment was 14 days. Replication was 16 times. Main parameter observed was the change of body weight. Supporting parameter was food consumption. Data was analyzed by varians analysis with Completely Random Design. The result was the given of barbados nut’s seed decrease mouse body weight.